A PLANAR n⁺ –n–n⁺ GaAs DIODE WITH GaInAs-BASED GRADED-GAP ACTIVE SIDE BOUNDARYN - V. O. Zozulia; O. V. Botsula; K. H. Prykhodko (Radio Physics and Radio Astronomy)
Subject and Purpose. The generation of millimeter-wave oscillations by a planar GaAs diode with active side boundary (ASB) is considered. The diode structure is placed on a semiconductor semi-insulating substrate and represents a GaAs channel approximately 1μm long. Its lateral surface carries a semiconductor element based on a graded-gap GaInAs layer electrically connected to the anode. The work seeks to assess the oscillation efficiency and the maximum output power of the diode oscillator loaded with a single-circuit resonator, determine the oscillation frequency cut-off, and estimate how the energy and frequency characteristics of the diode are influenced by the impact ionization and GaInAs spatial distribution in the graded-gap layer.